Incisional hernia after liver transplantation: Risk factors, management strategies and long-term outcomes of a cohort study. (June 2020) - Cos, Heidy; Ahmed, Ola; Garcia-Aroz, Sandra; Vachharajani, Neeta; Shenoy, Surendra; Wellen, Jason R.; Doyle, Maria MB.; Chapman, William C.; Khan, Adeel S.
Abstract: Introduction: Incisional hernias (IH) develop in up to 40% of liver transplant (LT) recipients and can contribute to considerable morbidity. Materials and methods: A single center retrospective review of a prospectively maintained LT database was conducted to identify all patients diagnosed with IH after LT during a 13-year study period (2003–2015). Analyzed data included patient demographics, LT details, incidence and timing of IH, risk factors, management strategies and long-term outcomes. Results: During the 13-year study period, IH was diagnosed in 16.7% (163/976) of LT recipients after a median of 19.6 months (range 6.7–49.5 months) from transplant surgery. Identified risk factors for developing IH included male gender (p < 0.001) while acute cellular rejection (ACR) was found to be negatively associated with the risk of developing IH (p = 0.014). Acute incarceration/strangulation was seen in 4 patients with IH while the remaining (n = 159) presented with non-emergent symptoms. Surgical repair was undertaken in 70/163 (43%) IH patients after medical optimization when possible (open repair 83%, mesh use 90%). IH recurrence rate was 14.3% (10/70) with comparable rates in no-mesh and with-mesh repairs (42.9% vs. 11.3%; p = 0.057) and open (15.8%) and laparoscopic (9.1%) approaches (p = 0.68). Conclusion: IH is a late complication following LT and male gender is a consistent predictive marker. Acute presentation is infrequent and elective repair can be planned in most patients allowing for risk factor optimization to ensure promising long-term outcomes. Highlights: Longer survival in transplant recipients merits the awareness of long-term morbidity. Incisional hernia repairs are particularly complex with prior liver transplantation. Recipients require careful optimization if incisional hernia repairs are advised. Male sex consistently predicts incisional hernia occurrence. Cellular rejection correlations affirm unique immune constructs in recipients.